Draft Annual Plan 2008-09 Volume -I Government of Punjab Department of Planning - Planning Commission (Planning Commission, 2008)
Punjab entered the Eleventh Five Year Plan after a sluggish performance in the Tenth Plan period. the economy of Punjab grew at an annual average of 5.08 % consistently under-performing against the national average of 7.8%. After the first two years of recession, the State economy showed some signs of recovery posting annual growth of over 5 percent. Stagnation of the State’s economic growth in the past one decade has been a major concern for both planners as well as the political executive. The State was a frontrunner in the story of the India’s development since Independence scripting for itself an enviable record that continues to form benchmarks for the rest of the country.
Government of Punjab Department of Planning